Converting Chemical Energy Into Electricity through a Functionally Cooperating Device with Diving–Surfacing Cycles. (21st August 2014) - Song, Mengmeng; Cheng, Mengjiao; Ju, Guannan; Zhang, Yajun; Shi, Feng
<x xml:space="preserve">Abstract</x> A smart device that can dive or surface in aqueous medium has been developed by combining a pH‐responsive surface with acid‐responsive magnesium. The diving–surfacing cycles can be used to convert chemical energy into electricity. During the diving‐surfacing motion, the smart device cuts magnetic flux lines and produces a current, demonstrating that motional energy can be realized by consuming chemical energy of magnesium, thus producing electricity. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>